Factors contribute to employees’ adaptive performance a case of Telekom Malaysia, Melaka / Nur Farah Diyana Norsaidi - Norsaidi, Nur Farah Diyana (Faculty of Business and Management, 2018)
Adaptive performance is a aspects of phenomenon that require the organization to respond and adapt with change. The organization need to respond with changing of new environments that can give beneficial for firm performance. It can see that, today’s organization facing with dynamic and changing environment. So that with the nature of today’s organization, adaptive performance can play important role in increasing the productivity and effectiveness of the organization and also the employees. This paper investigate the factors contribute to adaptive performance among the employees in Telekom Malaysia, Melaka. This study used main data collection method by using a questionnaire from the employees at Telekom Malaysia, Melaka to determine the significant factors that can contribute to adaptive performance in the organization. The total population is 168 employees and from the total population, the sample size of 113 respondents was chosen using convenience sampling. The findings of this study for independent variables “Learning Orientation” and “Career Advancement” has support the hypotheses and significantly related with adaptive performance in the organization. But independent variable “Emergent Change” do not support the hypotheses and not significantly related with adaptive performance. So that the organization needs to have planned change in order to make the employees have awareness and do preparation to adapt with changing of new environment. For further study, it is suggested to change the factors and consider other variables.